Comparative study on lightning fatality rate in Malaysia between 2008 and 2017 - A Rahim, Syakura; Ab Kadir, Mohd Zainal Abidin; Gomes, Chandima; Abu Bakar, Elistina; Cooper, Mary Ann (IEEE, 2018)
Statistics of lightning fatalities and injuries are difficult to obtain as mandatory reporting of such events is seldom required. As a result, many cases will not be in official records. However, for injury prevention efforts and calling a government's attention to these as a serious problem, information on numbers and more vulnerable locations are important. In this study, Gomes-Kadir equation was used to estimate the annual lightning deaths in Malaysia using lightning density and sociological factors. The recorded data shows a lightning fatality rate of 12.5 deaths yr-1 with 4 deaths per ten-million population yr-1. The empirical formula estimates 20.9 deaths yr-1 and 6.7 dptm yr-1. Under-reporting of death events and the lack of consideration of topological factors in Gomes-Kadir equation have been highlighted as the reasons behind this discrepancy.